Fertigation with Pseudomonas putida and Bacillus subtilis: impact on growth and productivity of off-season quinoa grown in coastal Peru - Quello Huamani, Antony Arturo (2026)
Quinoa (Chenopodium quinoa Willd.) is a nutritionally valuable crop adapted to adverse agroclimatic conditions, but its production in arid regions such as the Peruvian coast is limited by water scarcity, low soil fertility, and heat stress. Plant growth-promoting rhizobacteria from Pseudomonas and Bacillus offer a sustainable strategy to improve growth and yield. This study evaluated the impact of fertigation with Pseudomonas putida (P3 strain) and Bacillus subtilis (BacF strain) on the growth and yield of the Salcedo INIA quinoa variety cultivated out of season under arid environment. A split-plot design was implemented, in which the main-plot factor was microbial inoculation [inoculated (+) vs. non-inoculated (−)], while the subplot factor was synthetic fertilization (75% vs. 100% of the recommended NPK dose). Inoculation was performed at two time points during the crop cycle at a concentration of 1 × 10⁹ CFU mL⁻¹, whereas fertigation was applied at four-day intervals. Rhizobacterial inoculation significantly improved plant biometric characteristics, resulting in a 12% increase in dry biomass accumulation. Photosynthetic capacity increased, as indicated by higher leaf area index and SPAD values than uninoculated plants. Thus, the main effect of inoculation was the significant increase of yield potential (i.e. panicle weight increasing by 12% and thousand-grain weight increasing by 19%) with yield improvements significant at both fertilization levels. Despite these positive effects, high temperatures (>30 °C) during the growing season limited commercial yields [(+)100%: 2.20 ± 0.30 t ha⁻¹, (+)75%: 1.42 ± 0.19 t ha⁻¹, (-)100%: 1.50 ± 0.30 t ha⁻¹, (+)75%: 1.02 ± 0.13 t ha⁻¹]. This reduction is likely due to heat stress during flowering, which may have compromised pollen viability and grain set efficiency. The findings suggest that P. putida (P3 strain) and B. subtilis (BacF strain) are promising biotechnological tools for improving quinoa productivity in arid climates.